Child Health and Mortality Prevention Surveillance (CHAMPS): Manhiça site description, Mozambique [version 1; peer review: 2 approved] - Fabíola Fernandes; Maria Maixenchs; Inácio Mandomando; Charfudin Sacoor; Ariel Nhacolo; Pio Vitorino; Rita Mabunda; Khátia Munguambe; Edgar Jamisse; Quique Bassat; Marcelino Garrine; Elísio Xerinda; et al. (Gates Open Research, 2023)
The Manhiça Health Research Centre (Manhiça HDSS) was established in 1996 in Manhiça, a rural district at Maputo Province in the southern part of Mozambique with approximately 49,000 inhabited households, a total population of 209.000 individuals, and an annual estimated birth cohort of about 5000 babies. Since 2016, Manhiça HDSS is implementing the Child Health and Mortality Prevention Surveillance (CHAMPS) program aiming to investigate causes of death (CoD) in stillbirths and children under the age of 5 years using, among other tools, the innovative post-mortem technique known as Minimally Invasive Tissue sampling (MITS). Both in-hospital and community pediatric deaths are investigated using MITS. For this, community-wide socio-demographic approaches (notification of community deaths by key informants, formative research involving several segments of the community, availability of free phone lines for notification of medical emergencies and deaths, etc.) are conducted alongside to foster community awareness, involvement and adherence as well as to compute mortality estimates and collect relevant information of health and mortality determinants. The main objective of this paper is to describe the Manhiça Health and Demographic Surveillance System (HDSS) site and the CHAMPS research environment in place including the local capacities among its reference hospital, laboratories, data center and other relevant areas involved in this ambitious surveillance and research project, whose ultimate aim is to improve child survival through public health actions derived from credible estimates and understanding of the major causes of childhood mortality in Mozambique.